USE OF MODERN TECHNOLOGIES IN THE SYSTEM OF EDUCATION - Juraeva Nargiza Oltinboevna; Nuriddinova Ferangiz Shamsiddin kizi (Western European Studies, 2025)
This article explores the meaning, definitions, origin stories, and the circumstances and motivations behind the use of pedagogical technologies and interactive methods in contemporary education. There are also descriptions of the conditions, benefits, and uses of various approaches. A vast amount of pedagogy and methodology-related materials are examined.
Keywords: student; teacher; qualification